Personal Branding Konten Kreator Muda dalam Video YouTube: Analisis Semiotika Charles Sanders Peirce pada Video "Satu Hari Bersama Siswa Kelas 12 SMA di Indonesia" - Romadhoni, Achmad; Mahmudi, Marwan; Umami, Zahrotul (Marcommers : Jurnal Marketing Communication and Advertising, 2024)
This study aims to analyze the personal branding built by Zahid Azmi Ibrahim in his YouTube video content through the semiotic approach of Charles Sanders Peirce. As a young content creator, Zahid presents an educational and productive self-image, traced through visual and verbal signs in the video "A Day with a 12th Grade High School Student in Indonesia." This research uses a descriptive qualitative method with Peirce's sign analysis and Peter Montoya's eight personal branding concepts as a theoretical framework. The results show that Zahid builds a strong personal brand through consistent content, a unique communication style, and an educational narrative close to student life. The personal branding effectively fosters a positive perception among his audience